2018
DOI: 10.1016/j.radphyschem.2017.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometric comparison of swift heavy ion-induced and anaerobic thermal degradation of polymers

Abstract: Mass spectrometric comparison of swift heavy ion-induced and anaerobic thermal degradation of polymers, Radiation Physics and Chemistry,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Additionally, in those experiments, it was common to use a pretreatment to promote the enzymatic attack of the PE. The proposed mechanism included the formation of free radicals from tertiary carbons, with the production of CH 4 and H 2 [ 59 ]. It was also shown that fungi could produce pits and erosions in plastics [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in those experiments, it was common to use a pretreatment to promote the enzymatic attack of the PE. The proposed mechanism included the formation of free radicals from tertiary carbons, with the production of CH 4 and H 2 [ 59 ]. It was also shown that fungi could produce pits and erosions in plastics [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…43 Generally, the attack of free radical on PE produces methane and hydrogen gas under UV and visible-light irradiation. 44 UV light (400−290 nm) determines the life of MPs in outdoor applications while UV quanta have energies from 3.1 to 4.3 eV according to 72−97 kcal/mol, suggesting that they have energy for chemical bond breakage. Thermal decomposition of PE does not take place at a temperature below 100 °C without sunlight, whereas the role of photo-oxidation is to initiate the chain reactions (Figure 1b1).…”
Section: Natural Degradation Mechanism Of Microplasticsmentioning
confidence: 99%
“…PE may comprise a small number of unsaturated bonds that are oxidized by O 3 , NOx, or other radicals, transforming it into a stable carbonyl group . Generally, the attack of free radical on PE produces methane and hydrogen gas under UV and visible-light irradiation . UV light (400–290 nm) determines the life of MPs in outdoor applications while UV quanta have energies from 3.1 to 4.3 eV according to 72–97 kcal/mol, suggesting that they have energy for chemical bond breakage.…”
Section: Natural Degradation Mechanism Of Microplasticsmentioning
confidence: 99%
“…This is typical in MO thin film processing where N incorporation is difficult. [59][60][61] Unique is the case of PAA. Although this polymer is thermally labile, as seen by TGA, both the film C and N content remains very large, again with the reduction of N versus the theoretical value being greater (≈4×) than that of C (only ≈10%).…”
Section: In 2 O 3 :Polymer Blend Films Microstructure and Chemical Co...mentioning
confidence: 99%